Effects of suspended micro- and nanoscale particles on zooplankton functional diversity of drainage system reservoirs at an open-pit mine - Goździejewska, Anna Maria; Gwoździk, Monika; Kulesza, Sławomir; Bramowicz, Mirosław; Koszałka, Jacek (Scientific reports, 2019)
Water from mining drainage is turbid because of suspensions. We tested the hypothesis that the chemical composition as well as shape and size of particles in suspensions of natural origin affect the density and functional diversity of zooplankton. The suspensions were analyzed with atomic force microscopy (AFM), energy dispersive X-ray spectroscopy (EDS), scanning electron microscopy (SEM), and optical microscopy. Elements found in the beidellite clays were also identified in the mineral structure of the particles. As the size of the microparticles decreased, the weight proportions of phosphorus, sulfur, and chlorine increased in the suspensions. These conditions facilitated the biomass growth of large and small microphages and raptorials. As the size of the nanoparticles decreased, the shares of silicon, aluminum, iron, and magnesium increased. These conditions inhibited raptorials the most. Ecosystem functionality was the highest with intermediate suspension parameters, which were at the lower range of the microphase and the upper range of the nanophase. The functional traits of zooplankton demonstrate their potential for use as sensitive indicators of disruptions in aquatic ecosystems that are linked with the presence of suspensions, and they facilitate gaining an understanding of the causes and scales of the impact of suspensions.